THE ANALYSIS OF JOKO WIDODO, PRABOWO SUBIANTO, AND NADIEM MAKARIM SPEECH’S IN SPEECH ACT AND THE FUNCTION OF THE EXPRESSION OF THE CORONA VIRUS - Suparto, Windy Puspitasari (Scientia: Jurnal Hasil Penelitian, 2020)
This aimed to describe the use of speech acts in the form of locutionary acts, illocutionary acts, perlocutionary acts, and expressive speech acts used by corona virus topic as the hot news. This research used descriptive qualitative method. The subject of this research are Ir. H. Joko Widodo, Nadiem Anwar Makarim, B.A., M.B.A. who had been joining KompasTV Program at Channel Youtube and H. Prabowo Subianto Djojohadikusumo who had been joining Garuda Siaga RI Facebook Page channel. The technique of collecting data was using free listening comprehension, video, and writing. The researcher took three of them as the subject. There are two kinds of instruments used in this research are observation and recorded. Observation with the passive observer where the writer used video recorder to record of the speech and also transcribing. The instrument was an indirect observation. The results showed that there were types of locutionary acts, illocutionary acts, perlocutionary acts, and functions of expressive speech acts consisting of expressing thanksgiving, complaining, praising, apologized and motivate.